Who needs nature? The influence of employee speciesism on nature-based need satisfaction and subsequent work behavior. - Tang, Pok Man; Klotz, Anthony C.; McClean, Shawn T.; Wang, Yating; Song, Zhaoli; Ng, Chin Tung Stewart (Journal of Applied Psychology, 2023)
Scholars have long upheld the notion that exposure to nature benefits individuals. Recently, organizational researchers have theorized that these benefits extend to the workplace, leading to calls for organizations to incorporate contact with nature into employees' jobs. However, it is unclear whether the effects of nature are strong enough to meaningfully impact employee performance, thereby justifying organizations' investments in them. In this research, we draw on self-determination theory to develop a theoretical model predicting that exposure to nature at work satisfies employees' psychological needs (i.e., needs for autonomy, relatedness, and competence) and positively affects their subsequent task performance and prosocial behavior. In addition, we theorize that the effects of nature on need satisfaction are weaker in employees higher on speciesism (i.e., the belief that humans are superior to other forms of life). We test these predictions with a mixed-method approach comprised of an online experiment in the United States (Study 1), a field experiment in Hong Kong (Study 2), a multiwave, multisource field study in Taiwan (Study 3), and a multiwave, multisource field study (with objective performance scores) in New Zealand (Study 4). Overall, our findings largely support our theoretical model. (PsycInfo Database Record (c) 2023 APA, all rights reserved).